Kawasaki disease and the environment: an enigmatic interplay - Aggarwal, Ridhima; Pilania, Rakesh Kumar; Sharma, Saniya; Kumar, Amit; Dhaliwal, Manpreet; Rawat, Amit; Singh, Surjit (Frontiers in Immunology, 2023)
Kawasaki disease (KD) is a common systemic vasculitis of childhood. Although it has been almost 6 decades since Dr. Tomisaku Kawasaki reported the first case series of KD, the underlying cause remains a mystery. KD is a self-limiting disease. However, a dreaded complication is development of coronary artery abnormalities (CAAs). KD is the most common cause of acquired heart disease in children in the developed world and is being increasingly reported from developing countries too. Over the years, significant observations have been made about epidemiology of KD. It usually affects children below 5, has male preponderance and has significantly higher incidence in North-East Asian countries. While several hypotheses have been proffered for etiology of KD, none have been conclusive. These include associations of KD epidemics in Japan and the United Stated with changes in tropospheric wind patterns suggesting wind-borne agents, global studies showing peaks of incidence related to season, and increased rates in populations with a higher socioeconomic profile related to hygiene hypothesis and vaccination. Furthermore, self-limiting, febrile nature of KD suggests an infectious etiology, more so with sudden decline noted in cases in Japan with onset of COVID-19 mitigation measures. Finally, single nucleotide polymorphisms have been identified as possible risk alleles in patients with KD and their significance in the pathogenesis of this disease are also being defined. The purpose of this review is to elucidate puzzling associations of KD with different environmental factors. Looking at patterns associated with KD may help us better predict and understand this disease.